Eugenol improves salt tolerance via enhancing antioxidant capacity and regulating ionic balance in tobacco seedlings - Xu, Jiaxin; Wang, Tingting; Sun, Changwei; Liu, Peng; Chen, Jian; Hou, Xin; Yu, Tao; Gao, Yun; Liu, Zhiguo; Yang, Long; Zhang, Li (Frontiers in Plant Science, 2024)
Salt stress inhibits plant growth by disturbing plant intrinsic physiology. The application of exogenous plant growth regulators to improve the plant tolerance against salt stress has become one of the promising approaches to promote plant growth in saline environment. Eugenol (4-allyl-2methoxyphenol) is the main ingredient in clove oil and it is known for its strong antioxidant and antimicrobial activities. Eugenol also has the ability of inhibiting several plant pathogens, implying the potential use of eugenol as an environmentalfriendly agrichemical. However, little is known about the possible role of eugenol in the regulation of plant tolerance against abiotic stress. Therefore, here we investigated the effectiveness of phytochemical eugenol in promoting salt tolerance in tobacco seedlings through physiological, histochemical, and biochemical method. The seedling roots were exposed to NaCl solution in the presence or absence of eugenol. Salt stress inhibited seedling growth , but eugenol supplementation effectively attenuated its effects in a dose-dependent manner, with an optimal effect at 20 µM. ROS (reactive oxygen species) accumulation was found in seedlings upon salt stress which was further resulted in the amelioration of lipid peroxidation, loss of membrane integrity, and cell death in salt-treated seedlings. Addition of eugenol highly suppressed ROS accumulation and reduced lipid peroxidation generation. Both enzymatic and non-enzymatic antioxidative systems were activated by eugenol treatment. AsA/DHA and GSH/GSSG were also enhanced upon eugenol treatment, which helped maintain redox homeostasis upon salinity. Eugenol treatment resulted in an increase in the content of osmoprotectants (e.g. proline, soluble sugar and starch) in salt-treated seedlings. Na+ levels decreased significantly in seedlings upon eugenol exposure. This may result from the upregulation of the expression of two ionic transporter genes, SOS1 (salt-hypersensitive 1) and NHX1 (Na+ /H+ anti-transporter 1). Hierarchical cluster combined correlation analysis uncovered that eugenol induced salt tolerance was mediated by redox homeostasis and maintaining ionic balance in tobacco seedlings. This work reveals that eugenol plays a crucial role in regulating plant resistant physiology. This may extend its biological function as a novel biostimulant and opens up new possibilities for improving crop productivity in the saline agricultural environment.